+0  
 
0
172
1
avatar+2509 

Help.

NotSoSmart  Oct 31, 2017
 #1
avatar+87714 
+1

2x + 3y   = 11    →  3y  = 11 - 2x        (1)

3x + 3y   = 18      (2)

 

Put (1) into (2)    and we have

 

3x  + 11 - 2x  =  18        subtract  11 from both sides and simplify

 

x =  7          and using  (2)  to find y, we have that

 

3 (7)  + 3y  = 18

21  + 3y = 18     subtract 21 from both sides

3y   =  - 3       divide both sides by 3

y  =  -1 

 

 

cool cool cool 

CPhill  Oct 31, 2017
edited by CPhill  Oct 31, 2017

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.